Suitability of Lee Codes to fit Mather, Fillipov and Hybrid Dense Plasma Focus Machines Current Waveform. - Arwinder, Singh*; Teh, Thiam Oun; Saw, Sor Heoh; Lee, Sing (The Abdus Salam International Centre for Theoretical Physics, 2019)
There are several types of Dense Plasma Focus (DPF) machines with different anode geometry. It is a real advantage if the various types of machines could be simulated using one code. This is of particular importance from the comparative point of view. This paper examines the use of the Lee Code to model a Mather type Plasma Focus(PF), a Filippov type PF and a hybrid type PF. The test for model fit is to check if the computed current trace could be fitted to the experimentally measured trace of current. It is found that the Mather type PF is modelled well and that the hybrid PF is also fitted well. The Filippov type PF could be fitted only for the lift-off and the first part of the radial sub-phase using the standard Lee Code, although it has been reported that a different code called the ML (Modified Lee) has been developed and is used to fit Filippov typed PF’s. The conclusion is that the Lee Code in its current form can be used to model Mather type PF and hybrids, but needs extensive modification such as to Siahpoush’s ML version in order to accurately portray all phases of the Filippov type PF.